2014
DOI: 10.1063/1.4903469
|View full text |Cite
|
Sign up to set email alerts
|

High-speed tapping-mode atomic force microscopy using a Q-controlled regular cantilever acting as the actuator: Proof-of-principle experiments

Abstract: We present the proof-of-principle experiments of a high-speed actuation method to be used in tappingmode atomic force microscopes (AFM). In this method, we do not employ a piezotube actuator to move the tip or the sample as in conventional AFM systems, but, we utilize a Q-controlled eigenmode of a cantilever to perform the fast actuation. We show that the actuation speed can be increased even with a regular cantilever. © 2014 AIP Publishing LLC. [http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In water, we did not obtain significant variance in the Q-factors due to high viscous damping. The ratio of the second eigenmode resonance to the fundamental one is greatly increased for reshaped cantilevers which makes them preferable in the actuatorless HS-AFM imaging [12,13]. If the original cantilever is in rectangular shape, it is difficult to lower the Q-factor further for highspeed imaging in air since there is not enough material left to remove.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In water, we did not obtain significant variance in the Q-factors due to high viscous damping. The ratio of the second eigenmode resonance to the fundamental one is greatly increased for reshaped cantilevers which makes them preferable in the actuatorless HS-AFM imaging [12,13]. If the original cantilever is in rectangular shape, it is difficult to lower the Q-factor further for highspeed imaging in air since there is not enough material left to remove.…”
Section: Discussionmentioning
confidence: 99%
“…In the recently proposed fast actuation method [12,13], e.g., it is desired to have a low Q-factor for the fundamental eigenmode and high Q-factors for the higher eigenmodes. Also, an increased separation of fundamental and higher eigenmode resonances improves the quality of the acquired topography in this method.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the imaging speed can be increased further by using cantilevers with higher resonance frequencies. We have already implemented the proposed highspeed method and performed the proof-of-principle experiments on a commercial AFM system [40]. This method will indeed minimize the time spent for dynamic AFM imaging experiments without requiring special or small cantilevers.…”
Section: Resultsmentioning
confidence: 99%
“…It is challenging to achieve high-speed TM imaging because an increase of the speed can cause a loss of the tip–sample interaction and/or the annihilation of the cantilever tapping vibration, particularly when the imaging size is large. Existing efforts on high-speed TM imaging [ 6 9 ] only led to a speed increase up to three times at the cost of a substantially (over five times) increased imaging force. By using the AMLM imaging mode, it is aimed to achieve high-speed dynamic-mode AFM imaging while maintaining the tip–sample interaction force similar as that in low-speed TM imaging.…”
Section: Introductionmentioning
confidence: 99%